2015
DOI: 10.5152/tjbh.2015.1669
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Classification of Breast Carcinoma: From Traditional, Old-Fashioned Way to A New Age, and A New Way

Abstract: Breast carcinoma comprises a group of diseases with specific clinical, histopathologic and molecular properties. Traditional classification use morphology to divide tumors into separate categories with differing behavior and prognosis. However, there are limitations of traditional classification systems, and new molecular methods are expected to improve classification systems. Molecular subtypes of breast carcinomas have been characterized in the last 11 years, and have been studied extensively. Much of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
130
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(176 citation statements)
references
References 63 publications
1
130
0
5
Order By: Relevance
“…Bunlar: Luminal tip A ve B, Normal, HER-2 pozitif meme kanseri ve bazal hücre benzeri meme kanserleridir. 1 Bazal hücre benzeri meme kanserleri normal meme dokusunda bulunan bazal veya myoepitelyal hücrelerin özelliklerini taşır ve agresif seyirlidir. Çoğu yüksek dereceli olup proliferasyon indeksi yüksektir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bunlar: Luminal tip A ve B, Normal, HER-2 pozitif meme kanseri ve bazal hücre benzeri meme kanserleridir. 1 Bazal hücre benzeri meme kanserleri normal meme dokusunda bulunan bazal veya myoepitelyal hücrelerin özelliklerini taşır ve agresif seyirlidir. Çoğu yüksek dereceli olup proliferasyon indeksi yüksektir.…”
Section: Discussionunclassified
“…Meme kanseri, kadınlarda en sık görülen kanser türü olup, tüm kanserlerin yaklaşık %25-%30`unu oluşturarak akciğer kanserlerinden sonra ikinci sırada yer alır. 1 Kansere bağlı mortalitenin %18'inden sorumludur. Uzun yıllar histoloji ve morfolojinin ön planda iken, günümüzde aynı histolojik bulgulara sahip olup aynı tedavi uygulanan hastaların seyirlerinin farklı olabildiği görülmüş, ve bu nedenle morfolojinin yanı sıra moleküler belirteçlerin de prognoz üzerine etkileri dikkat çekmeye başlamıştır.…”
Section: Introductionunclassified
“…With the advancements of new molecular techniques, it has been demonstrated that breast cancer is not a single disease but a heterogeneous one that comprise various molecular phenotypes characterized by specific behavior and prognosis (17). Molecular classification divides patients into subgroups based on their various gene expression including luminal A, luminal B, HER2 and basallike tumors (17). This classification not only has a valuable contribution to the management of patients with this malignancy but also represents a step forward in the new era of personalized therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is traditionally classified by the clinicopathologic features, including histopathological type, tumor grade and tumor stage (TNM), and biomarker receptor status, together with the characteristics of patients (e.g. age and menopausal status) [18,19].…”
Section: Molecular Classification Of Breast Cancermentioning
confidence: 99%